2019
DOI: 10.1007/s00198-019-05190-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between chronic kidney disease, falls, and fractures: a systematic review and meta-analysis

Abstract: Patients with chronic kidney disease (CKD) are more likely to experience falls and fractures due to renal osteodystrophy and the high prevalence of risk factors for falls. However, it is not well established how great the risk is for falls and fractures for the different stages of CKD compared to the general population. The objective of this systematic review and meta-analysis was to assess whether, and in which degree, CKD was associated with falls and fractures in adults. A systematic search in PubMed, Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 58 publications
(161 reference statements)
2
48
0
1
Order By: Relevance
“…Indeed, although QFracture includes falls as an input, it also includes other risk factors for falls (such as diabetes) that may partially capture the effect of falls on fracture risk. Because CKD has now been recognized as a risk factor for falls in some studies, this might explain the underperformance of Garvan in CKD patients . Second, because discrimination of any fracture by prediction models is generally lower than MOF, one may also hypothesize that the prediction of a different fracture outcome by Garvan (any fracture) compared to FRAX and QFracture (MOF) could explain this finding.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, although QFracture includes falls as an input, it also includes other risk factors for falls (such as diabetes) that may partially capture the effect of falls on fracture risk. Because CKD has now been recognized as a risk factor for falls in some studies, this might explain the underperformance of Garvan in CKD patients . Second, because discrimination of any fracture by prediction models is generally lower than MOF, one may also hypothesize that the prediction of a different fracture outcome by Garvan (any fracture) compared to FRAX and QFracture (MOF) could explain this finding.…”
Section: Discussionmentioning
confidence: 58%
“…Musculoskeletal and connective tissue disorders occurred in one patient, an 80-year-old female from the NDD-CKD nephrology treatment group. The osteoporotic fracture was reported by the treating physician and was not positively adjudicated as HP; it is to be noted that patients with CKD are prone to fractures due to renal osteodystrophy, which is itself caused by disturbances in metabolic and hormone levels such as parathyroid hormone and vitamin D [51,52]. In our pooled analysis, reported symptomatic HP was rare.…”
Section: Discussionmentioning
confidence: 67%
“…While Kistler et al [14] and Paliwal Note: a 2 "fear of falling" variables were added (not at all concerned vs other; fairly concerned vs other) Abbreviations: CI confidence interval, CKD chronic kidney disease, GDS geriatric depression score, IADL instrumental activities of daily living, OR odds ratio, SPPB short physical performance battery et al [15] demonstrated an increased odds ratio for falls in relation to CKD defined on the basis of clinical history and without reporting eGFR, a recent meta-analysis by Goto et al [32] could not find a clear relationship between eGFR values and accidental fall risk. Nevertheless, a trend for worsening eGFR increasing accidental falls risk was observed, as well as a significant association between low eGFR and fractures resulting from accidental falls [32]. Additionally, CKD may not represent a risk factor on itself, but rather associated variables, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CKD may not represent a risk factor on itself, but rather associated variables, e.g. reduced functional status, may mediate its detrimental effects [32]. The finding that patients with more severe stages of CKD are associated with coexisting conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%